2017
DOI: 10.3389/fpls.2016.02032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Overexpression of WRI1 and Hemoglobin Genes on the Seed Oil Content of Lepidium campestre

Abstract: The wild species field cress (Lepidium campestre), belonging to the Brassicaceae family, has potential to be developed into a novel oilseed- and catch crop, however, the species needs to be further improved regarding some important agronomic traits. One of them is its low oil content which needs to be increased. As far as we know there is no study aiming at increasing the oil content that has been reported in this species. In order to investigate the possibility to increase the seed oil content in field cress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…is a potential global regulator of de novo fatty acid biosynthesis that specifies the regulatory action of the direct target of LEC2 [97]. Overexpression of the transcription factor WRI1, which controls the expression of genes involved in lipid metabolism, including glycolysis and fatty acid biosynthesis, increased seed oil content by 10-20% compared to the wild type [40,90,[98][99][100][101]. LEC1 function was partially dependent on ABI3, FUS3 and WRI1 in the regulation of fatty acid biosynthesis; both LEC1 and LEC1-like genes were acted as key regulators to coordinate the expression of fatty acid biosynthetic genes [92].…”
Section: Soybean Fatty Acid Composition Biosynthesis and Transcriptiomentioning
confidence: 99%
“…is a potential global regulator of de novo fatty acid biosynthesis that specifies the regulatory action of the direct target of LEC2 [97]. Overexpression of the transcription factor WRI1, which controls the expression of genes involved in lipid metabolism, including glycolysis and fatty acid biosynthesis, increased seed oil content by 10-20% compared to the wild type [40,90,[98][99][100][101]. LEC1 function was partially dependent on ABI3, FUS3 and WRI1 in the regulation of fatty acid biosynthesis; both LEC1 and LEC1-like genes were acted as key regulators to coordinate the expression of fatty acid biosynthetic genes [92].…”
Section: Soybean Fatty Acid Composition Biosynthesis and Transcriptiomentioning
confidence: 99%
“…Further studies showed that AtWRI1 also plays a role in processes such as lipid assembly, storage, flowering time, seed development, embryo maturation, plant hormone regulation, and photosynthesis (Cernac et al, 2006;Kong et al, 2017;Li et al, 2015;Maeo et al, 2009;Wu et al, 2014). A number of other communications have also revealed orthologs of AtWRI1 being involved in plant oil biosynthesis (Adhikari et al, 2016;Bhattacharya et al, 2016;Chen et al, 2017;Ivarson et al, 2016;Kang et al, 2017;Kim et al, 2016;Liu et al, 2010;Ma et al, 2013;Pouvreau et al, 2011;Shen et al, 2010;Vanhercke et al, 2013;Wu et al, 2014;Yeap et al, 2017). For example, expression of the Brassica napus WRI1(BnWRI1) in Arabidopsis promoted between 10% and 40% increased seed oil content and led to larger seed and size mass (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with rapeseed, field cress is more suitable as a cover crop to prevent nutrient leaching due to its weaker growth vigour. However, it also has several drawbacks, such as low seed oil content, undesirable oil composition for food purposes or industrial feedstocks, and heavy pod shatter, which need to be improved before any commercialization of the species can take place (Ivarson et al 2016(Ivarson et al , 2017.…”
Section: Four Hypothetical Introductions Of New Cultivarsmentioning
confidence: 99%